Global Assessment of Dengue Virus-Specific CD4+ T Cell Responses in Dengue-Endemic Areas - Grifoni, Alba; Angelo, Michael A.; Lopez, Benjamin; O’Rourke, Patrick H.; Sidney, John; Cerpas, Cristhiam; Balmaseda, Angel; Silveira, Cassia G. T.; Maestri, Alvino; Costa, Priscilla R.; Durbin, Anna P.; Diehl, Sean A.; et al. (Frontiers in Immunology, 2017)
Background Dengue is a major public health problem worldwide. Assessment of adaptive immunity is important to understanding immunopathology and to define correlates of protection against dengue virus (DENV). To enable global assessment of CD4+ T cell responses, we mapped HLA-DRB1-restricted DENV-specific CD4+ T cell epitopes in individuals previously exposed to DENV in the general population of the dengue-endemic region of Managua, Nicaragua. Methods HLA class II epitopes in the population of Managua were identified by an in vitro IFNγ ELISPOT assay. CD4+ T cells purified by magnetic bead negative selection were stimulated with HLA-matched epitope pools in the presence of autologous antigen-presenting cells, followed by pool deconvolution to identify specific epitopes. The epitopes identified in this study were combined with those previously identified in the DENV endemic region of Sri Lanka, to generate a “megapool” (MP) consisting of 180 peptides specifically designed to achieve balanced HLA and DENV serotype coverage. The DENV CD4MP180 was validated by intracellular cytokine staining assays. Results We detected responses directed against a total of 431 epitopes, representing all 4 DENV serotypes, restricted by 15 different HLA-DRB1 alleles. The responses were associated with a similar pattern of protein immunodominance, overall higher magnitude of responses, as compared to what was observed previously in the Sri Lanka region. Based on these epitope mapping studies, we designed a DENV CD4 MP180 with higher and more consistent coverage, which allowed the detection of CD4+ T cell DENV responses ex vivo in various cohorts of DENV exposed donors worldwide, including donors from Nicaragua, Brazil, Singapore, Sri Lanka, and U.S. domestic flavivirus-naïve subjects immunized with Tetravalent Dengue Live-Attenuated Vaccine (TV005). This broad reactivity reflects that the 21 HLA-DRB1 alleles analyzed in this and previous studies account for more than 80% of alleles present with a phenotypic frequency ≥5% worldwide, corresponding to 92% phenotypic coverage of the general population (i.e., 92% of individuals express at least one of these alleles). Conclusion The DENV CD4 MP180 can be utilized to measure ex vivo responses to DENV irrespective of geographical location.